Factors associated with provision of smoking cessation support to pregnant women - a cross-sectional survey of midwives in New South Wales, Australia - Megan E. Passey; Jo M. Longman; Catherine Adams; Jennifer J. Johnston; Jessica Simms; Margaret Rolfe (BMC, 2020)
Abstract Background Smoking is the most important preventable cause of adverse pregnancy outcomes, but provision of smoking cessation support (SCS) to pregnant women is poor. We examined the association between midwives' implementation of SCS (5As - Ask, Advise, Assess, Assist, Arrange follow-up) and reported barriers/enablers to implementation. Methods On-line anonymous survey of midwives providing antenatal care in New South Wales (NSW), Australia, assessing provision of the 5As and barriers/enablers to their implementation, using the Theoretical Domains Framework (TDF). Factor analyses identified constructs underlying the 5As; and barriers/enablers. Multivariate general linear models examined relationships between the barrier/enabler factors and the 5As factors. Results Of 750 midwives invited, 150 (20%) participated. Respondents more commonly reported Asking and Assessing than Advising, Assisting, or Arranging follow-up (e.g. 77% always Ask smoking status; 17% always Arrange follow-up). Three 5As factors were identified- 'Helping', 'Assessing quitting' and 'Assessing dependence'. Responses to barrier/enabler items showed greater knowledge, skills, intentions, and confidence with Assessment than Assisting; endorsement for SCS as a priority and part of midwives' professional role; and gaps in training and organisational support for SCS. Nine barrier/enabler factors were identified. Of these, the factors of 'Capability' (knowledge, skills, confidence); 'Work Environment' (service has resources, capacity, champions and values SCS) and 'Personal priority' (part of role and a priority) predicted 'Helping'. Conclusion The TDF enabled systematic identification of barriers to providing SCS, and the multivariate models identified key contributors to poor implementation. Combined with qualitative data, these results have been mapped to intervention components to develop a comprehensive intervention to improve SCS.